PEMANFAATAN PELAYANAN SKRINING KANKER LEHER RAHIM DI RUMAH SAKIT UMUM DAERAH DR. ZAINOEL ABIDIN BANDA ACEH - , Adri IDiana ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Cervical cancer prevention programs in developed countries have been effective in reducing morbidity and mortality caused by this cancer. The incidence of cervical cancer in developing countries is 61/100,000 women while in developed countries it reaches only 11/100,000 women. One effort made to the cancer prevention is to perform cervical cancer screening. This screening can detect early changes of cervical cells that can prevent the diseaseâs serious progresses. However, the utilization of cervical cancer screening in developing countries is still very low due to many factors, including the availability of service facilities and human resources. Objective: To determine the overview of cervical cancer screening services utilization. Methods: This was a qualitative research with a case study design. Samples were taken using a purposive sampling. The main informants were women who utilized and did not utilized the pap smear services, health officers and decision-makers. The data was collected through Focus Group Discussions (FGDs), in-depth interviews and observation. The data analysis used a descriptive analytic method. Result: Facilities of pap smear services and supporting laboratory had been available. Cervical cancer screening services provided by the officers had met the existing rules. The women utilized the pap semar services driven by their need to health not by the information received from the officers. The officers had not been proactively given the health promotion and information. In addition, some reasons for women who had not utilized the pap smear services yet were that they were afraid and embarrased due to their lack of information about examination procedure